Detection of the recently emerged synthetic cannabinoid 5F–MDMB‐PICA in 'legal high' products and human urine samples. Issue 1 (24th May 2017) - Mogler, Lukas; Franz, Florian; Rentsch, Daniel; Angerer, Verena; Weinfurtner, Georg; Longworth, Mitchell; Banister, Samuel D.; Kassiou, Michael; Moosmann, Bjoern; Auwärter, Volker
Abstract : Indole or indazole‐based synthetic cannabinoids (SCs) bearing substituents derived from valine or tert ‐leucine are frequently abused new psychoactive substances (NPS). The emergence of 5F–MDMB‐PICA (methyl N ‐{[1‐(5‐fluoropentyl)‐1 H –indol‐3‐yl]carbonyl}‐3‐methylvalinate) on the German drug market is a further example of a substance synthesized in the context of scientific research being misused by clandestine laboratories by adding it to 'legal high' products. In this work, we present the detection of 5F–MDMB‐PICA in several legal high products by gas chromatography–mass spectrometry (GC–MS) analysis. To detect characteristic metabolites suitable for a proof of 5F–MDMB‐PICA consumption by urine analysis, pooled human liver microsome (pHLM) assays were performed and evaluated using liquid chromatography–tandem mass spectrometry (LC–MS/MS) and liquid chromatography quadrupole time‐of‐flight mass spectrometry (LC‐QToF‐MS) techniques to generate reference spectra of the in vitro phase I metabolites. The in vivo phase I metabolism was investigated by the analysis of more than 20 authentic human urine specimens and compared to the data received from the pHLM assay. Biotransformation of the 5‐fluoropentyl side chain and hydrolysis of the terminal methyl ester bond are main phase I biotransformation steps. Two of the identified main metabolites formed by methyl ester hydrolysis or mono‐hydroxylation at the indole ring system were evaluated as suitable urinary biomarkers and discussed regarding the interpretation of analytical findings. Exemplary analysis of one urine sample for 5F–MDMB‐PICA phase II metabolites showed that two of the main phase I metabolites are subject to extensive glucuronidation prior to renal excretion. Therefore, conjugate cleavage is reasonable for enhancing sensitivity. Commercially available immunochemical pre‐tests for urine proved to be unsuitable for the detection of 5F–MDMB‐PICA consumption. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Signals for metabolites of the SC 5F‐PB‐22 during routine LC‐MS/MS screening of urine specimens for SC metabolites were identified as metabolites of the novel synthetic cannabinoid SC 5F‐MDMB‐PICA by LC‐QToF‐MS analysis. In this study the detection 5F‐MDMB‐PICA in herbal blends adn the identification of phase I metabolites suitable for proving 5F‐MDMB‐PICA consumption by LC‐MS/MS and LC‐Q‐ToF‐MS analyses of authentic urine samples is reported. Commercial available immunochemical pre‐tests were tested for the detection of 5F‐MDMB‐PICA consumption.